RELIANCE ON AVOIDANCE COPING STRATEGY BY MILITARY PERSONNEL IN COMBAT - Kravchenko, Kateryna; Yutovets, Vasyl (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The article presents the findings of a theoretical review conducted to analyze the issues military personnel encounter when relying on the avoidance coping strategy in combat. The article also highlights the findings of empirical studies that allowed the authors to identify the correlations between the avoidance coping strategy and other psychological characteristics. In the opinion of the authors such correlations will significantly broaden the prevailing understanding of the research subject. Despite the relevance of the topic, especially in the context of the fullscale invasion taking place on the territory of Ukraine, the issue or reliance on avoidance coping strategy in military personnel is not well-studied. M e t h o d s . At this stage of the research the authors have relied on theoretical methods, mainly analysis, synthesis, generalization, comparison, and systematization. Strictly scientific and up-to-date references in both Ukrainian and English were analyzed. One of the empirical research methods used was the testing method.R e s u l t s . Having analyzed the research findings obtained by both Ukrainian and foreign scientists on the specifics of the avoidance strategy, the authors have concluded that the interest of the global scientific community towards the subject of the study would be significantly higher if a serviceman avoiding his combat duties and other negative effects of avoidance would be considered to be a radically negative manifestation of the avoidance coping strategy. Reliance on the avoidance coping strategy in military personnel in combat depends on the following factors: serviceman's character traits and personality type (including personality accentuations), psychological defense mechanisms, resilience level, thinking style, personality orientation, levels of subjective control, emotional burnout, empathy, communicative aggression, meaning of life, communication and organizational skills, proneness to conflict behavior, reactions related to combat stress and post-traumatic stress disorder, and individual ability to adapt.C o n c l u s i o n s . The research findings allowed the authors not only to validate the relevance of the selected research topic and achieve the set research objective, but also to outline the further research areas. These possible future research areas include interpreting the obtained results (especially in the context of radically negative manifestation of the avoidance such as the refusal to performed combat duties), thoroughly studying the external factors impacting the reliance on the mentioned coping strategy in combat, developing a psychodiagnostic methodology for predicting the proclivity for the reliance on the aforementioned coping strategy, as well as drafting recommendations for military psychologists on how to best work with military personnel suffering from the negative effects of the avoidance coping strategy.
Keywords: coping strategies, avoidance coping strategy, military personnel, combat zone, correlations in the avoidance coping strategy